A service evaluation of a specialist community palliative care occupational therapy service. (December 2014) - Phipps, Kerrie; Cooper, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Background Occupational therapy aims to maximize patients' independence and is thus particularly relevant in palliative care where a loss of function is both common and distressing for patients. However, there is evidence that health professionals have a limited understanding of its role and remit, with the consequence that timely referrals are not made. Method A service evaluation was undertaken to establish colleagues' understanding of the palliative care occupational therapy service and its perceived benefit to patients in one local primary care area. A mixed methods approach was used, combining an online survey and focus groups. One hundred people were invited to complete the questionnaire, with a 58% response rate. Twenty-five people subsequently participated in two focus groups. Results Participants believed that the service achieved its aims. The main reasons for referral to the occupational therapy service were for the provision of equipment, or advice about equipment to support independent community living. Facilitating patients' preferred place of care was ranked next in importance. Participants did not feel that they were sufficiently aware of the full range of occupational therapy services available, and suggested that the provision of education and information would be effective in raising awareness of the remit of the specialist occupational therapy service. Conclusion From the professional service users' perspective, the specialist community palliative care occupational therapy service makes a valuable contribution to maintaining patients' independence, comfort, and quality of life, and is associated with supporting patients' preferred place of care. Areas highlighted for development include clear communication pathways, and education and information strategies regarding the role of the palliative care occupational therapist.